Impact of the 2008 Global Recession on air quality over the United States: Implications for surface ozone levels from changes in NOx emissions. Issue 17 (5th September 2016) - Tong, Daniel; Pan, Li; Chen, Weiwei; Lamsal, Lok; Lee, Pius; Tang, Youhua; Kim, Hyuncheol; Kondragunta, Shobha; Stajner, Ivanka
Abstract: Satellite and ground observations detected large variability in nitrogen oxides (NO x ) during the 2008 economic recession, but the impact of the recession on air quality has not been quantified. This study combines observed NO x trends and a regional chemical transport model to quantify the impact of the recession on surface ozone (O3 ) levels over the continental United States. The impact is quantified by simulating O3 concentrations under two emission scenarios: business‐as‐usual (BAU) and recession. In the BAU case, the emission projection from the Cross‐State Air Pollution Rule is used to estimate the "would‐be" NO x emission level in 2011. In the recession case, the actual NO2 trends observed from Air Quality System ground monitors and the Ozone Monitoring Instrument on the Aura satellite are used to obtain "realistic" changes in NO x emissions. The model prediction with the recession effect agrees better with ground O3 observations over time and space than the prediction with the BAU emission. The results show that the recession caused a 1–2 ppbv decrease in surface O3 concentration over the eastern United States, a slight increase (0.5–1 ppbv) over the Rocky Mountain region, and mixed changes in the Pacific West. The gain in air quality benefits during the recession, however, could be quickly offset by the much slower emission reduction rate during the post‐recession period. Key Points: The 2008 economic recession significantly affected air quality over the United States It is feasible to combine computer models and ground/space observations to quantify the air quality effect of economic recessions Timely updates of emission inventories become increasingly important during major socioeconomic events for air quality management